The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.9734/ijecc/2022/v12i330644
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Mustard as Influenced by Date of Sowing and Varieties in Western Rajasthan, India

Abstract: An experiment was conducted at agricultural research station, SKRAU, Bikaner during rabi season of 2017-18 to evaluate yield of mustard as influenced by date of sowing and varieties in western Rajasthan. The treatment consisted of three dates of sowings viz., 10th October, 25th October and 9th November were kept in main plot and five varieties viz. RH-119, NRCHB-101, RGN-48, RH-749 and Laxmi was kept as sub plot replicated thrice in split plot design. Crop sown on 25th October recorded significantly higher see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…So, this was depended on varietal trait and plant inherent capacity. It was reported a variable trend of straw yield production among 5 Indian mustard varieties with 3 different sowing dates during winter season (34).…”
Section: Stover Yieldmentioning
confidence: 99%
“…So, this was depended on varietal trait and plant inherent capacity. It was reported a variable trend of straw yield production among 5 Indian mustard varieties with 3 different sowing dates during winter season (34).…”
Section: Stover Yieldmentioning
confidence: 99%
“…Inappropriate dry matter translocation or senescence related metabolic impairment or both may lead to delayed maturity according to Priya (2020). Recently, Shivran et al, (2022) reported that phenophases of mustard like days to 50% flowering, initiation of siliqua etc were shortened except days to maturity due to high temperature. Further poor performance of crop due to delayed sowing resulted in shorter growing time which delays maturity and results in yield losses.…”
Section: Phenological Responsementioning
confidence: 99%